Contradictions of economic policy in the context of new risks and challenges in the development of the world economy - E. N. Smirnov (Управление)
The relevance of the problems considered in the article is associated with the growth of uncertainty and increased turbulence in the development of the world economy in recent years, as well as with the ambiguous impact of this instability on the economies of individual countries. These new trends have actualized the problems of economic policy, the analysis of which is the purpose of our study. These problems are connected both with the restoration of the previous growth rates and the choice of optimal instruments of fiscal and monetary policy, as well as counteracting the volatility of world prices and the instability inherent in commodity markets. One of the objectives of the study is to assess the approaches of individual countries in terms of their response to the crisis phenomena of recent years, to determine the main directions for counteracting the growth in the debt burden of countries, tools to curb inflation in the context of unprecedentedly tight financial conditions, as well as mechanisms for macroprudential regulation. As one of the results of the study, the author proves the growing differentiation of economic policies in the context of individual countries, limiting the sustainable recovery of the world economy, which is exacerbated by the ongoing instability of international trade and disruptions in global value chains. In addition, the author concluded that volatile world energy and food prices make traditional economic policies more uncertain and force countries to use alternative economic regulation tools, in particular, those related to changing the practice of applying policy rates to curb inflation, new approaches to the implementation of the tasks of the climate agenda and labor market policy.